Conceptual Model for Innovation in the Approach of Market - Oriented Strategies - Bermúdez-Hernández, Jonathan; Valencia-Arias, Alejandro; Montaño-Arias, Walter Mauricio (Indian Journal of Marketing, 2021)
Market orientation refers to a set of cross-sectional functional processes and activities aimed at satisfying customer expectations through a continuous assessment of their needs. This includes processing information to generate market intelligence from the entire organization with respect to said needs: current and future. This study proposed a market orientation model (based on the one introduced by Narver and Slater) that allows organizations to identify the most critical factors for innovation in their market-oriented approach. A self-administered questionnaire was distributed to 307 employees at different companies in Medellin, Colombia, and the data resulting from exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to build the model proposed in this study. It was identified that the two main variables related to innovation in market-oriented strategies are adaptation to changes in customer preferences and proactive behavior in the work environment.